2002
DOI: 10.1175/1520-0442(2002)015<2233:agrtes>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric GCM Response to Extratropical SST Anomalies: Synthesis and Evaluation*

Abstract: We examine the advances in our understanding of extratropical atmosphere-ocean interaction over the past decade and a half, focusing on the atmospheric response to sea surface temperature anomalies. The main goal of the paper is to assess what was learned from general circulation model (GCM) experiments over the recent two decades or so. Observational evidence regarding the nature of the interaction and dynamical theory of atmospheric anomalies forced by surface thermal anomalies are reviewed. We then proceed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

48
526
2
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 581 publications
(614 citation statements)
references
References 110 publications
(174 reference statements)
48
526
2
1
Order By: Relevance
“…This suggests a pathway via which SST anomalies may influence the development of synoptic systems: SST anomalies influence thickness anomalies, which in turn alters thickness gradients, thermal wind, and the potential for systems to develop. Similar relationships based on SST's and their gradients have been articulated in observational (Kushnir et al, 2002) and modeling studies (Frederiksen and Balgovind, 1994;Kushnir et al, 2002;Ummenhofer et al, 2008).…”
Section: Enso/iod Classificationsupporting
confidence: 59%
“…This suggests a pathway via which SST anomalies may influence the development of synoptic systems: SST anomalies influence thickness anomalies, which in turn alters thickness gradients, thermal wind, and the potential for systems to develop. Similar relationships based on SST's and their gradients have been articulated in observational (Kushnir et al, 2002) and modeling studies (Frederiksen and Balgovind, 1994;Kushnir et al, 2002;Ummenhofer et al, 2008).…”
Section: Enso/iod Classificationsupporting
confidence: 59%
“…The opposite is true for positive SSTA. This is one of the salient features of observed extratropical SSTA and their associated atmospheric patterns, as described in Frankignoul [1985] and Kushnir et al [2002].…”
Section: Horizontal Structure Of the Air-sea System During Wwr And Nomentioning
confidence: 62%
“…Overall, the SSTA shows continuous decreases (increases) in the positive (negative) non-WWR years without WWR (Figure 2c and 2d). Thus, the differences between 1951, 1956, 1965, 1966, 1968, 1971, 1974Negative 1959, 1960, 1977, 1978, 1983, 1985, 1986, 1994, 1996, 1998, 1999Non-WWR Positive 1950, 1952, 1953, 1954, 1955, 1957, 1962, 1963, 1967, 1969, 1972, 1976, 1982, 1989, 1990, 1991, 1993, 2000, 2002Negative 1958, 1961, 1964, 1970, 1973, 1975, 1979, 1980, 1981, 1984, 1987, 1988, 1992, 1995, 2001…”
Section: Methodsologymentioning
confidence: 99%
See 1 more Smart Citation
“…A long-standing question has been the extent to which anomalous extra-tropical SSTs feed back to affect the atmosphere (e.g. Rodwell et al, 1999;Robinson, 2000;Kushnir et al, 2002). It has been shown that AGCMs forced with observed SST anomalies can reproduce the annular mode behaviour that induced these extra-tropical SST anomalies (Rodwell et al, 1999).…”
Section: Goga Model-data Comparisonmentioning
confidence: 99%